2019
DOI: 10.1016/j.opelre.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The operation of THz quantum cascade laser in the region of negative differential resistance

Abstract: We investigate the light-current-voltage characteristics and emission spectra of 2.3 THz quantum cascade laser operating in the negative differential resistance (NDR) region. It was shown that the formation of electric field domains (EFDs) leads to a large number of discontinuities on the current-voltage and the total optical power on current characteristics. Measurements of emission spectra at different current (before the NDR region and in the NDR region) shows that the formation of EFDs results in decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…The most common CW-radiation sources are quantum cascade lasers, 10,11 high-speed transistors, and diodes. 12,13 Tunable CW THz waves may be obtained by backward-wave oscillators, 14 parametric conversion, 15 and photomixing and frequency multiplication.…”
Section: Thz Instrumentationmentioning
confidence: 99%
“…The most common CW-radiation sources are quantum cascade lasers, 10,11 high-speed transistors, and diodes. 12,13 Tunable CW THz waves may be obtained by backward-wave oscillators, 14 parametric conversion, 15 and photomixing and frequency multiplication.…”
Section: Thz Instrumentationmentioning
confidence: 99%
“…In devices with more tendency for intramodule leakage due to lower radiative barriers such as Device 2 (wafer VB0837 in Albo et al [8], Tables 1 and 2), hot electrons could relax more easily through leakage paths (as scattering from the ULL to level 7 in Figure 1 in [8]) and the instability was much more moderate. The main reason for the laser instability may be the formation of electric field domains [9,10] in the NDR region in the absence of parallel leakage channels.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we studied different realizations of the SWDP scheme using different barrier compositions than the original contribution and analyzed their performance. We found that the lasers are limited by a lasing instability [9,10] that becomes significant as the temperature increases.…”
Section: Introductionmentioning
confidence: 87%
“…Отметим, что максимальная плотность тока J на ВАХ достигается вблизи напряжения V 1 = 53 мВ, когда уровень инжектора 1 ′ совпадает с верхним лазерным уровнем 4. При дальнейшем увеличении напряжения уровень 4 становится ниже уровня 1 ′ , что соответствует отрицательной ветви ВАХ, где генерация не стабильна и, как показано в работе [21], Исследования вольт-амперных характеристик (ВАХ) и зависимостей интегральной интенсивности излучения от тока накачки и температуры изготовленных ТГц ККЛ с двойным металлическим волноводом проводились в импульсном режиме (длительность импульса 500 нс, частота повторения 100 Гц). Для питания структур использовался специально изготовленный электронный ключ, позволяющий получать импульсы заданных длительности, скважности и амплитуды, а также измерять напряжение и ток, проходящий через лазер.…”
Section: Introductionunclassified